IMAM ZARKASYI DAN KONSEP PENDIDIKAN HIDDEN CURIKULUM - Echsanuddin Echsanuddin (Institut Nahdlatul Ulama Tasikmalaya, 2022)
Imam Zarkasyi (1910-1985) of Gontor Ponorogo East Java along with his two other brothers called Trimurti (the three founders of Pondok Modern Gontor), both KH. Ahmad Sahal (1901-1977) and KH. Zainuddin Fannani (1905- 1967) were the most dedicated figures on the modern Indonesian Islamic boarding schools education system. Kiai Zarkasyi was not only well known in Indonesia but even in the Muslim world. This article attempts to gain a deeper understanding about Zarkasyi‘s educational philosophy and his hidden curriculum; and how the patterns of its implementation in the educational system processes thus provides a significant influence on his discipliners, with a qualitative approach in the form of naturalistic phenomenology through literature study and empirical experience as a means of checking the validity of confirmatory data. The findings revealed that all educational activities in Pondok Modern Gontor has governed by a soul by design which maintained formal curriculum (intracurricular and extra-curricular) called written curriculum. On the top of all, the study discoveres the patterns of hidden curriculum applicable as the affect of edicational process under the formal curriculum. It took place in many models such as learning by instruction, learning by doing, and so on. Here, in fact, there is the strength and success of education in dormitories, such as in Pondok Modern Gontor which has a significant direct effect on the students, who in turn has an effect on the nation character building and the religion.